Graded morphologies and the performance of PffBT4T-2OD:PC71BM devices using additive choice - Gaspar, Hugo (2021)
The impact of several solvent processing additives (1-chloronaphthalene, methylnaphthalene, hexadecane, 1-phenyloctane, and p-anisaldehyde), 3% v/v in o-dichlorobenzene, on the performance and morphology of poly[(5,6-difluoro-2,1,3-benzothiadiazol-4,7-diyl)-alt-(3,3"'-di(2-octyldodecyl)-2,2 ',5 ',22033,5 '',2"'-quaterthiophen-5,5"'-diyl)] (PffBT4T-2OD):[6,6]-phenyl-C71-butyric acid methyl ester (PC71BM)-based polymer solar cells was investigated. Some additives were shown to enhance the power conversion efficiency (PCE) by ~6%, while others decreased the PCE by ~17-25% and a subset of the additives tested completely eliminated any power conversion efficiency and the operation as a photovoltaic device. Grazing-Incidence Wide Angle X-ray Scattering (GIWAXS) revealed a clear stepwise variation in the crystallinity of the systems when changing the additive between the two extreme situations of maximum PCE (1-chloronaphthalene) and null PCE (hexadecane). Small-Angle Neutron Scattering (SANS) revealed that the morphology of devices with PCE ~0% was composed of large domains with correlation lengths of ~30 nm, i.e., much larger than the typical exciton diffusion length (~12 nm) in organic semiconductors. The graded variations in crystallinity and in nano-domain size observed between the two extreme situations (1-chloronaphthalene and hexadecane) were responsible for the observed graded variations in device performance.